Biochemical genetics of some Indian fishes - Menezes, Maria R; Quasim, S Z (Indian Journal of Fisheries, 2011)
In this paper an attempt has been made to evaluate the present status ofthe biochemical genetic research in fishes. At the same time, we have given the importance of this field of study and also indicated what we regard as the most fruitful areas for future research.